PENDEKATAN MULTIDISIPLIN SEBAGAI MODEL INTEGRASI ILMU - Nur Melinda (PT. Saha Kreasi Indonesia, 2025)
Multidisciplinary approaches are a model that integrates various disciplines to comprehensively analyze and solve complex problems. This model transcends the traditional boundaries between fields of study, such as natural sciences, social sciences, and humanities, to create a more holistic framework. Its goal is to combine diverse methodologies, theories, and perspectives to produce a richer and deeper understanding of a phenomenon, which would be impossible to obtain from a single viewpoint alone. Thus, this model encourages innovation in research, increases the social relevance of scientific findings, and enables the creation of more sustainable solutions. Nevertheless, there are several challenges in implementing a multidisciplinary model. The main obstacles often arise from differences in terminology and methodology between disciplines, as well as institutional structures in academia that tend to favor specialization. However, with strong collaboration and effective communication, these challenges can be overcome, making the multidisciplinary approach a key to building a model of scientific integration that is more adaptive and responsive to the complexities of the modern world.